Factors influencing study outcomes in recent literatüre on distal radial fracture treatments - AKGÜLLE, AHMET HAMDİ; BEKİROĞLU, GÜLNAZ NURAL (My University, 2023)
The main tools used by an orthopaedic surgeon for managing distal radial fracture treatment are recent literature and treatment guidelines. The aim of the present study was to find which factors within the study design influence study outcomes the most. Trials in three major databases (PubMed, Scopus, Embase) comparing surgical and non-surgical treatment options for adolescent and adult distal radial fractures with their original data, between 2013 and 2021, were included. The selected 47 studies were classified according to their outcomes. The relationship between study characteristics and outcomes was statistically analysed. It was more likely to find no difference in outcomes between volar locking plate and less invasive treatments when the sample size was above 100, follow-up was more than 1 year and functional assessments were used. A small sample size and short follow-up time affect study outcomes in favour of a volar locking plate. Readers should focus on the design criteria and read the full text of the studies before making any conclusions.Level of evidence:III.Keywords:Adult; distal radius; fracture; study bias; treatment.
Keywords: Tıp; Cerrahi Tıp Bilimleri; Ortopedi ve Travmatoloji; Sağlık Bilimleri; Temel Tıp Bilimleri; Biyoistatistik ve Tıp Bilişimi; Medicine; Surgery Medicine Sciences; Orthopedics and Traumatology; Health Sciences; Fundamental Medical Sciences; Biostatistics and Medical Informatics; Klinik Tıp (MED); Klinik Tıp; CERRAHİ; TIBBİ BİLİŞİM; ORTOPEDİ; TIP, GENEL & DAHİLİ; Clinical Medicine (MED); CLINICAL MEDICINE; SURGERY; MEDICAL INFORMATICS; ORTHOPEDICS; MEDICINE, GENERAL & INTERNAL; Ayak Bakımı; Genel Sağlık Meslekleri; Patofizyoloji; Temel Bilgi ve Beceriler; Değerlendirme ve Teşhis; Cerrahi; Ortopedi ve Spor Hekimliği; Dahiliye; Tıbbi Bilişim; Aile Sağlığı; Tıp (çeşitli); Genel Tıp; Podiatry; General Health Professions; Pathophysiology; Fundamentals and Skills; Assessment and Diagnosis; Surgery; Orthopedics and Sports Medicine; Internal Medicine; Health Informatics; Family Practice; Medicine (miscellaneous); General Medicine